Importance of Medicinal Plants in Mullaitivu District - Athavan, V.; Pelastina, A.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
There are various type of medicinal plants available in Sri Lanka.. This District consists of different eco-systems such as forest land, shrub land, coconut plantation, agriculture land and water bodies. Total land area is 251,690 hectares. Approximately 167,850 hectares which is 64.1% of the total land area consists of forest. This district has a coastal belt of 70 km and four lagoons namely Mathalan, Nanthikadal, Nayaru & Kokulai which are very suitable for growing plants. There are five mangroves and 15 mangrove associated plants identified in these lagoons. The lifestyles of ancestors in Sri Lanka were closely related with nature. It is noted that they have used the names of medicinal plants to name villages and reservoirs. My objective of the study is to identify importance of medicinal plants in Mullaitivu district. Frequent field visits were made to the areas during January 2017-June 2017. The data was collected directly visiting the areas and conducting interview with people who resides there, state the study area. The results revealed that 90 villages are named based on the medicinal plants. Plants without any use would not be concerned by anybody. Therefore adequate knowledge should be important to the general public who are living to the study area on sustainable use by identified medicinal plants named to the villages. We must take immediate action to recultivating plant which are going to verge of extension and also obtained available information on medicinal plants.
Keywords: Medicinal plants; Mullaitivu district; Villages; Mangroves